THE MECHANISM OF SETTLEMENT OF GROSS VIOLANCE OF HUMAN RIGHTS ABUSES BY THE INTERNATIONAL CRIMINAL COURT - Natsif, Fadli Andi (Journal of Humanity, 2014)
Although there were differences in the mechanism of enforcement against Human Rights violations or Human Rights crimes among national law (Law Court of Human Rights) and international law (Statute of Rome 1998) between the two jurisdictions, however, have a relationship. Jurisdiction in the Statute of Rome was said to be only as a complement to the jurisdiction of the national law. When there are indications of "unwilling and unable" to national jurisdiction in processing the cases of Human Rights violations which are also regulated in the Statute of Rome, then this is the reason the Roman Statute of the jurisdiction can apply. In addition, previous State should ratify the Statute of Rome became part of national law.Â Â